2018
DOI: 10.1096/fj.201801241r
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine sensitivity screening highlights BMP4 pathway signaling as a therapeutic opportunity in ER + breast cancer

Abstract: Despite the success of approved systemic therapies for estrogen receptor (ER)α-positive breast cancer, drug resistance remains common. We hypothesized that secreted factors from the human tumor microenvironment could modulate drug resistance. We previously screened a library of 297 recombinant-secreted microenvironmental proteins for the ability to confer resistance to the anti-estrogen fulvestrant in 2 ER breast cancer cell lines. Herein, we considered whether factors that enhanced drug sensitivity could be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Components of the TME including stromal cells and secreted factors have been implicated in drug resistance to both chemotherapeutics and targeted agents in a multitude of cancer types [20, 21]. Similarly, TME components such as secreted factors, hypoxia and acidity have been shown to contribute to enhancing drug sensitivity in cancer [4042]. Determining potential interplay between SLFN11 expression, the tumor microenvironment, and sensitization to chemotherapy represents a logical and clinically important next step.…”
Section: Discussionmentioning
confidence: 99%
“…Components of the TME including stromal cells and secreted factors have been implicated in drug resistance to both chemotherapeutics and targeted agents in a multitude of cancer types [20, 21]. Similarly, TME components such as secreted factors, hypoxia and acidity have been shown to contribute to enhancing drug sensitivity in cancer [4042]. Determining potential interplay between SLFN11 expression, the tumor microenvironment, and sensitization to chemotherapy represents a logical and clinically important next step.…”
Section: Discussionmentioning
confidence: 99%
“…And screening data showed that bone morphogenetic protein (BMP) 4 could inhibit cell growth and synergize with endocrine therapy and CDK4/6 inhibitors. By upregulation of p21, BMP4 enhanced sensitivity to CDK4/6 inhibitors in estrogen-resistant cells (Figure 2) 86. Furthermore, transcriptomic features of BMP4 signaling predicted an improved biological response to the palbociclib combined with an aromatase inhibitor 86.…”
Section: Mechanisms Of Resistance and Combined Treatment To Allevimentioning
confidence: 99%
“…By upregulation of p21, BMP4 enhanced sensitivity to CDK4/6 inhibitors in estrogen-resistant cells (Figure 2) 86. Furthermore, transcriptomic features of BMP4 signaling predicted an improved biological response to the palbociclib combined with an aromatase inhibitor 86. Fangchinoline is an alkaloid with cytotoxic, anti-inflammatory and antioxidant properties.…”
Section: Mechanisms Of Resistance and Combined Treatment To Allevimentioning
confidence: 99%
“…It is well known that certain signaling, such as HER2, crosstalks with ER signaling and the targeted drug sensitivity is enhanced by ER blockade (30). Signaling of BMPs is also known to crosstalk with that of ER (31,32). Therefore, it was of interest to investigate the association of ER positivity and BMP expression.…”
Section: Resultsmentioning
confidence: 99%